Preparation method of organic silicon anticorrosive paint
By combining quaternized cyclotetrasiloxane, functionalized polysiloxane and modified nanotitanium dioxide in the coating, the defects of traditional coatings in self-healing, corrosion prevention, antibacterial and flame retardant are solved, and the defects of traditional coatings are achieved. Efficient coating performance improvement and structural protection.
Patent Information
- Application Number
- CN202411358292.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Traditional coatings have defects in self-healing, corrosion prevention, antibacterial and flame retardant, especially in the face of microbial erosion, fire sources and high temperatures, resulting in performance degradation and safety hazards.
Using a preparation method of silicone anticorrosion coating, quaternized rings are prepared by reacting heptamethylcyclotetrasiloxane, N,N-dimethylvinylamine and 4-chloromethylbenzene boric acid pennamol ester Tetrasiloxane and react with octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane to produce functionalized polysiloxane, combined with modified nanotitanium dioxide and polyamide curing agent to form coatings with antibacterial, high temperature resistance and flame retardant properties.
The self-healing, flame retardant, antibacterial and anti-UV aging properties of the paint are achieved, which extends the structural life and maintains good performance after multiple stress cycles, which significantly improves the corrosion resistance and safety of the paint.
Smart Images

Figure BDA0005064257840000091 
Figure BDA0005064257840000101 
Figure BDA0005064257840000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a method for preparing an organosilicon anticorrosive coating. Background Art
[0002] In the current industrial and architectural fields, coatings are the first line of defense against environmental erosion, and their importance is self-evident. In recent years, with the advancement of science and technology and the upgrading of social needs, the limitations of traditional coating technology have become increasingly obvious. During the service life of coatings, the performance of coatings may be affected by external forces such as local scratches or stress-related macro cracks that cause coating damage. If these local damages are not repaired in a timely and effective manner, they will form channels for corrosive media to pass through and corrode the internal structure. It can be seen that traditional coatings lack self-repairing and anti-corrosion functions.
[0003] In addition, microbial erosion may also cause the performance of the coating to degrade, so it is necessary to combine antibacterial functions on the coating to play a protective role. Most coatings also lack flame retardancy. Once they encounter a fire source, they cannot effectively prevent the spread of flames, which poses a serious safety hazard in flammable and explosive environments such as petrochemicals and electricity. Therefore, a high temperature resistant, UV resistant, flame retardant coating is needed to make up for the above defects and extend the life of the structure. The organosilicon anticorrosive coating prepared by the present invention has excellent anticorrosion, self-repairing, flame retardant and antibacterial properties. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an organosilicon anti-corrosion coating to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The invention discloses an organosilicon anti-corrosion coating, which comprises the following components in parts by mass: 40-50 parts of epoxy resin, 10-15 parts of functionalized polysiloxane, 20-30 parts of xylene, 10-12 parts of modified nano titanium dioxide and 20-30 parts of polyamide curing agent.
[0007] As an optimization, the functionalized polysiloxane is prepared by first reacting heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and 4-chloromethylphenylboronic acid pinacol ester to obtain quaternized cyclotetrasiloxane, and then reacting quaternized cyclotetrasiloxane, octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
[0008] As an optimization, the modified nano titanium dioxide is prepared by reacting titanium dioxide nanosheets, aniline and (3-aminophenyl)phosphonic acid.
[0009] A method for preparing an organosilicon anticorrosive coating comprises the following steps:
[0010] (1) Heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and toluene are mixed in a mass ratio of 1:1.1-1.3:20-30, heated to 80°C and stirred for 1-1.5h under nitrogen protection at a stirring speed of 200-300r / min, then heated to 100-110°C, 0.2-0.3 times the mass of heptamethylcyclotetrasiloxane of chloroplatinic acid is added, the reaction is continued for 7-8h, and toluene is removed by vacuum rotary evaporation at 0.09MPa and 60°C to obtain tertiary amine-containing cyclotetrasiloxane;
[0011] (2) Under nitrogen protection, 4-chloromethylphenylboronic acid pinacol ester, tertiary amine-containing cyclotetrasiloxane, potassium iodide, potassium carbonate and toluene are mixed uniformly in a mass ratio of 1:1.1-1.2:0.1-0.2:1.5-1.7:10-12, heated to 80° C., stirred for reaction for 1-2 h, and stirred at a speed of 200-300 r / min. Toluene is removed by reduced pressure rotary evaporation at 0.09 MPa and 60° C. to obtain quaternized cyclotetrasiloxane;
[0012] (3) Under nitrogen protection, octamethylcyclotetrasiloxane, quaternized cyclotetrasiloxane, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are mixed in a mass ratio of 1:1.2-1.3:0.8-0.9, stirred at 50°C for 10-20 min, a macroporous strongly acidic cation exchange resin of 0.3-0.5 times the mass of octamethylcyclotetrasiloxane is added, the temperature is raised to 60°C, the reaction is continued for 5-6 h, the filtrate is filtered and collected, and vacuum rotary evaporation is performed at 0.09 MPa and 60°C for 3 h to obtain a functionalized polysiloxane;
[0013] (4) After mixing titanium dioxide nanosheets, polyvinyl pyrrolidone and ethanol for 3-5 minutes, aniline, (3-aminophenyl)phosphonic acid and 1 mol / L sulfuric acid aqueous solution were added, and stirred at a speed of 300-400 r / min for 30-40 minutes, 15 mg / mL ammonium persulfate aqueous solution was added, and stirred at 0°C for 20-22 hours, filtered and dried at 80°C for 6-8 hours to obtain modified nano titanium dioxide;
[0014] (5) Weigh the following components by mass: 40-50 parts of epoxy resin, 10-15 parts of functionalized polysiloxane, 20-30 parts of xylene, 10-12 parts of modified nano-titanium dioxide, and 20-30 parts of polyamide curing agent, and stir the above components for 3-5 minutes to obtain an organosilicon anti-corrosion coating.
[0015] As an optimization, the model of the macroporous strongly acidic cation exchange resin in step (3) is HND-580.
[0016] As an optimization, the preparation method of the titanium dioxide nanosheets in step (4) is: adding hydrofluoric acid to butyl titanate and stirring for 20-30 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 300-400r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water for 3-5 times, and drying at 60°C for 10-12 hours to obtain titanium dioxide nanosheets.
[0017] As an optimization, the amounts of the titanium dioxide nanosheets, polyvinyl pyrrolidone, ethanol, aniline, (3-aminophenyl)phosphonic acid, 1 mol / L sulfuric acid aqueous solution, and 15 mg / mL ammonium persulfate aqueous solution in step (4) are as follows: by mass: 1 part of titanium dioxide nanosheets, 0.6-0.8 parts of polypyrrolidone, 500-550 parts of ethanol, 0.3-0.5 parts of aniline, 0.3-0.5 parts of (3-aminophenyl)phosphonic acid, 20-25 parts of 1 mol / L sulfuric acid aqueous solution, and 50-60 parts of 5 mg / mL ammonium persulfate aqueous solution.
[0018] As an optimization, the model of the epoxy resin in step (5) is E51; the model of the polyamide curing agent is 650.
[0019] As an optimization, the organosilicon anti-corrosion coating is prepared and used immediately; the method of using the organosilicon anti-corrosion coating is as follows: apply the coating on a polished and degreased tinplate, cure it at 80°C for 2h, and cure it at 100°C for 1h to obtain an organosilicon anti-corrosion coating.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] When preparing the organosilicon anticorrosion coating, the present invention firstly reacts heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and 4-chloromethylphenylboronic acid pinacol ester to obtain quaternized cyclotetrasiloxane, then reacts quaternized cyclotetrasiloxane, octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain functionalized polysiloxane; reacts titanium dioxide nanosheets, aniline and (3-aminophenyl)phosphonic acid to obtain modified nano titanium dioxide, and finally mixes epoxy resin, functionalized polysiloxane, xylene, modified nano titanium dioxide and polyamide curing agent to obtain the organosilicon anticorrosion coating.
[0022] Firstly, heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and 4-chloromethylphenylboronic acid pinacol ester are reacted to prepare quaternized cyclotetrasiloxane, the double bond on N,N-dimethylethyleneamine and the silicon-hydrogen bond on heptamethylcyclotetrasiloxane are combined by silicon hydrogen addition, and then the quaternized cyclotetrasiloxane is subjected to nucleophilic substitution with 4-chloromethylphenylboronic acid pinacol ester to generate quaternized cyclotetrasiloxane, and the quaternized cyclotetrasiloxane, octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are ring-opened to obtain amino-terminated functionalized polysiloxane, the phenylboronic acid pinacol ester on the side chain of the amino-terminated functionalized polysiloxane reacts with the hydroxyl group formed by the ring opening of the epoxy resin during the subsequent high-temperature curing process to generate borate ester, the quaternary ammonium salt structure on the side chain of the polysiloxane can give the coating certain antibacterial properties, and the silicon-oxygen structure of the main chain of the polysiloxane has excellent thermal stability and can give the coating high temperature resistance;
[0023] Secondly, titanium dioxide nanosheets, aniline and (3-aminophenyl)phosphonic acid are reacted to obtain modified nano titanium dioxide. The sheet structure of nano titanium dioxide can effectively block the corrosive medium in the air. Titanium dioxide itself has the function of absorbing ultraviolet rays, which can give the coating the performance of anti-ultraviolet aging. Titanium dioxide can also give the coating certain antibacterial properties due to its own photocatalytic activity. The polyaniline wrapped on the surface has unique anti-corrosion properties, especially for metal surfaces. The presence of polyaniline forms a dense metal oxide film at the interface between the metal and the polyaniline, thereby protecting the metal. The presence of (3-aminophenyl)phosphonic acid can not only give the coating flame retardant properties, but also electrostatically adsorb with quaternized polysiloxane, thereby increasing the dispersibility of the modified nano titanium dioxide in the subsequent mixing process of the coating components.
[0024] Finally, epoxy resin, functionalized polysiloxane, xylene, modified nano-titanium dioxide and polyamide curing agent are mixed to prepare silicone anti-corrosion coating. During the curing process of the coating, the amino groups at both ends of the polyamide curing agent and the functionalized polysiloxane can co-cure and cross-link the epoxy resin. The hydroxyl groups generated by the ring-opening reaction of the epoxy resin can react with the phenylboronic acid pinacol ester on the side chain of the functionalized polysiloxane to form borate esters. When the coating is cracked or broken by external force, the oxygen bridge originally connected to the boron atom is disconnected under the action of stress, releasing free alcohol groups and boric acid. These free alcohol groups and boric acid can recombine to form new borate ester bonds, giving the coating the ability to self-repair, so that it can still maintain good performance after experiencing multiple stress cycles. At the same time, the presence of borate esters can also synergistically flame retard with the phosphorus element in phosphoric acid, further improving the flame retardant properties of the coating. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The macroporous strongly acidic cation exchange resin used in the following examples and comparative examples is of model HND-580, the epoxy resin is of model E51, and the polyamide curing agent is of model 650.
[0027] Example 1
[0028] (1) Heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and toluene are mixed in a mass ratio of 1:1.1:20, heated to 80°C and stirred for 1 hour at a stirring speed of 300 r / min under nitrogen protection, then heated to 110°C, 0.2 times the mass of heptamethylcyclotetrasiloxane of chloroplatinic acid is added, the reaction is continued for 8 hours, and toluene is removed by vacuum rotary evaporation at 0.09 MPa and 60°C to obtain tertiary amine-containing cyclotetrasiloxane;
[0029] (2) Under nitrogen protection, 4-chloromethylphenylboronic acid pinacol ester, tertiary amine-containing cyclotetrasiloxane, potassium iodide, potassium carbonate and toluene are mixed uniformly in a mass ratio of 1:1.1:0.1:1.5:10, heated to 80°C, stirred for reaction for 2h, and stirred at a speed of 300r / min. Toluene is removed by vacuum rotary evaporation at 0.09MPa and 60°C to obtain quaternized cyclotetrasiloxane;
[0030] (3) Under nitrogen protection, octamethylcyclotetrasiloxane, quaternized cyclotetrasiloxane, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1.2:0.8, stirred at 50°C for 20 min, a macroporous strongly acidic cation exchange resin (0.3 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 60°C, the reaction was continued for 6 h, the filtrate was filtered and collected, and vacuum rotary evaporation was performed at 0.09 MPa and 60°C for 3 h to obtain a functionalized polysiloxane;
[0031] (4) Adding hydrofluoric acid to butyl titanate and stirring for 30 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 400 r / min, reacting in a polytetrafluoroethylene reactor at 180° C. for 24 hours, cooling to room temperature, washing with pure water 5 times, and drying at 60° C. for 12 hours to obtain titanium dioxide nanosheets, weighing 1 part of titanium dioxide nanosheets, 0.6 parts of polypyrrolidone, 500 parts of ethanol, 0.3 parts of aniline, and 0.03 parts of (3-aminophenyl)phosphonic acid by mass. .3 parts, 20 parts of 1 mol / L sulfuric acid aqueous solution, and 50 parts of 5 mg / mL ammonium persulfate aqueous solution; after mixing titanium dioxide nanosheets, polyvinyl pyrrolidone, and ethanol for 5 minutes, aniline, (3-aminophenyl)phosphonic acid, and 1 mol / L sulfuric acid aqueous solution were added, and stirred at a speed of 400 r / min for 40 minutes, 15 mg / mL ammonium persulfate aqueous solution was added, and stirred at 0°C for 22 hours, filtered, and dried at 80°C for 6-8 hours to obtain modified nano titanium dioxide;
[0032] (5) Weigh the following components by mass: 40 parts of epoxy resin, 10 parts of functionalized polysiloxane, 20 parts of xylene, 10 parts of modified nano-titanium dioxide, and 20 parts of polyamide curing agent, stir the above components for 5 minutes to obtain an organosilicon anti-corrosion coating, apply the organosilicon anti-corrosion coating on a polished and degreased tinplate, and cure it at 80°C for 2 hours and at 100°C for 1 hour to obtain an organosilicon anti-corrosion coating.
[0033] Example 2
[0034] (1) Heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and toluene are mixed in a mass ratio of 1:1.2:25, heated to 80°C and stirred for 1.3 hours at a stirring speed of 250 r / min under nitrogen protection, then heated to 105°C, 0.25 times the mass of heptamethylcyclotetrasiloxane of chloroplatinic acid is added, the reaction is continued for 7.5 hours, and toluene is removed by vacuum rotary evaporation at 0.09 MPa and 60°C to obtain tertiary amine-containing cyclotetrasiloxane;
[0035] (2) Under nitrogen protection, 4-chloromethylphenylboronic acid pinacol ester, tertiary amine-containing cyclotetrasiloxane, potassium iodide, potassium carbonate and toluene are mixed uniformly in a mass ratio of 1:1.15:0.15:1.6:11, heated to 80°C, stirred for reaction for 1.5h, and stirred at a speed of 250r / min. Toluene is removed by vacuum rotary evaporation at 0.09MPa and 60°C to obtain quaternary ammonium cyclotetrasiloxane;
[0036] (3) Under nitrogen protection, octamethylcyclotetrasiloxane, quaternized cyclotetrasiloxane, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1.25:0.85, stirred at 50°C for 15 min, a macroporous strongly acidic cation exchange resin (0.35 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 60°C, the reaction was continued for 5.5 h, the filtrate was filtered and collected, and vacuum rotary evaporation was performed at 0.09 MPa and 60°C for 3 h to obtain a functionalized polysiloxane;
[0037] (4) Add hydrofluoric acid to butyl titanate and stir for 25 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 350 r / min, and the reaction is carried out in a polytetrafluoroethylene reactor at 180°C for 24 hours. After cooling to room temperature, it is washed with pure water for 4 times and dried at 60°C for 11 hours to obtain titanium dioxide nanosheets. 1 part of titanium dioxide nanosheets, 0.7 parts of polypyrrolidone, 525 parts of ethanol, 0.4 parts of aniline, and (3-aminophenyl)phosphonic acid are weighed in parts by mass. 0.4 parts, 22 parts of 1 mol / L sulfuric acid aqueous solution, 55 parts of 5 mg / mL ammonium persulfate aqueous solution; after mixing titanium dioxide nanosheets, polyvinyl pyrrolidone and ethanol for 4 minutes, aniline, (3-aminophenyl)phosphonic acid and 1 mol / L sulfuric acid aqueous solution were added, stirred at a speed of 350 r / min for 35 minutes, 15 mg / mL ammonium persulfate aqueous solution was added, stirred at 0°C for 21 hours, filtered and dried at 80°C for 7 hours to obtain modified nano titanium dioxide;
[0038] (5) Weigh the following components by mass: 45 parts of epoxy resin, 13 parts of functionalized polysiloxane, 22 parts of xylene, 11 parts of modified nano-titanium dioxide, and 25 parts of polyamide curing agent, stir the above components for 4 minutes to obtain an organosilicon anti-corrosion coating, apply the organosilicon anti-corrosion coating on a polished and degreased tinplate, and cure it at 80°C for 2 hours and at 100°C for 1 hour to obtain an organosilicon anti-corrosion coating.
[0039] Example 3
[0040] (1) Heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and toluene are mixed in a mass ratio of 1:1.3:30, heated to 80°C and stirred for 1 hour at a stirring speed of 200 r / min under nitrogen protection, then heated to 100°C, 0.3 times the mass of heptamethylcyclotetrasiloxane of chloroplatinic acid is added, the reaction is continued for 7 hours, and toluene is removed by vacuum rotary evaporation at 0.09 MPa and 60°C to obtain tertiary amine-containing cyclotetrasiloxane;
[0041] (2) Under nitrogen protection, 4-chloromethylphenylboronic acid pinacol ester, tertiary amine-containing cyclotetrasiloxane, potassium iodide, potassium carbonate and toluene are mixed uniformly in a mass ratio of 1:1.2:0.2:1.7:12, heated to 80°C, stirred for reaction for 1 hour at a stirring speed of 200 r / min, and toluene is removed by reduced pressure rotary evaporation at 0.09 MPa and 60°C to obtain quaternized cyclotetrasiloxane;
[0042] (3) Under nitrogen protection, octamethylcyclotetrasiloxane, quaternized cyclotetrasiloxane, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1.3:0.9, stirred at 50°C for 10 min, a macroporous strongly acidic cation exchange resin (0.5 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 60°C, the reaction was continued for 5 h, the filtrate was filtered and collected, and the functionalized polysiloxane was obtained by vacuum rotary evaporation at 0.09 MPa and 60°C for 3 h;
[0043] (4) Adding hydrofluoric acid to butyl titanate and stirring for 20 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 300 r / min, reacting in a polytetrafluoroethylene reactor at 180° C. for 24 hours, cooling to room temperature, washing with pure water for 3 times, and drying at 60° C. for 10 hours to obtain titanium dioxide nanosheets, weighing 1 part of titanium dioxide nanosheets, 0.8 parts of polypyrrolidone, 50 parts of ethanol, 0.5 parts of aniline, and 0.03 parts of (3-aminophenyl)phosphonic acid by mass. .5 parts, 25 parts of 1 mol / L sulfuric acid aqueous solution, and 60 parts of 5 mg / mL ammonium persulfate aqueous solution; after mixing titanium dioxide nanosheets, polyvinyl pyrrolidone, and ethanol for 3 minutes, aniline, (3-aminophenyl)phosphonic acid, and 1 mol / L sulfuric acid aqueous solution were added, and stirred at a speed of 300 r / min for 30 minutes, 15 mg / mL ammonium persulfate aqueous solution was added, and stirred at 0°C for 20 hours, filtered, and dried at 80°C for 6 hours to obtain modified nano titanium dioxide;
[0044] (5) Weigh the following components by mass: 50 parts of epoxy resin, 15 parts of functionalized polysiloxane, 30 parts of xylene, 12 parts of modified nano-titanium dioxide, and 30 parts of polyamide curing agent, stir the above components for 3 minutes to obtain an organosilicon anti-corrosion coating, apply the organosilicon anti-corrosion coating on a polished and degreased tinplate, and cure it at 80°C for 2 hours and at 100°C for 1 hour to obtain an organosilicon anti-corrosion coating.
[0045] Comparative Example 1
[0046] The preparation method of the organosilicon anticorrosive coating of Comparative Example 1 differs from that of Example (2) in that there is no step (3). Step (3) is modified as follows: under nitrogen protection, octamethylcyclotetrasiloxane, tertiary amine-containing cyclotetrasiloxane, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are mixed in a mass ratio of 1:1.25:0.85, stirred at 50°C for 15 minutes, a macroporous strongly acidic cation exchange resin with a mass of 0.35 times that of octamethylcyclotetrasiloxane is added, the temperature is raised to 60°C, the reaction is continued for 5.5 hours, the filtrate is filtered and collected, and vacuum rotary evaporation is performed at 0.09 MPa and 60°C for 3 hours to obtain functionalized polysiloxane.
[0047] Comparative Example 2
[0048] The difference between the preparation method of the organosilicon anticorrosive coating of Comparative Example 2 and Example (2) is that step (4) is modified to add hydrofluoric acid to butyl titanate and stir for 25 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 350r / min, and the reaction is carried out in a polytetrafluoroethylene reactor at 180°C for 24 hours. After cooling to room temperature, it is washed with pure water 4 times and dried at 60°C for 11 hours to obtain titanium dioxide nanosheets. 1 part of titanium dioxide nanosheets and 1 part of polypyrrolidone are weighed by mass. 0.7 parts of ketone, 525 parts of ethanol, 0.4 parts of aniline, 22 parts of 1 mol / L sulfuric acid aqueous solution, and 55 parts of 5 mg / mL ammonium persulfate aqueous solution; after mixing titanium dioxide nanosheets, polyvinyl pyrrolidone and ethanol for 4 minutes, aniline and 1 mol / L sulfuric acid aqueous solution were added, and stirred at a speed of 350 r / min for 35 minutes, 15 mg / mL ammonium persulfate aqueous solution was added, and stirred at 0°C for 21 hours, filtered and dried at 80°C for 7 hours to obtain modified nano titanium dioxide.
[0049] Comparative Example 3
[0050] The preparation method of the silicone anti-corrosion coating of Comparative Example 3 differs from that of Example (2) in that step (5) is modified to weigh the following components in parts by mass: 45 parts of epoxy resin, 13 parts of functionalized polysiloxane, 22 parts of xylene, and 25 parts of polyamide curing agent, and the above components are stirred for 4 minutes to obtain the silicone anti-corrosion coating, and the silicone anti-corrosion coating is applied on a polished and degreased tinplate, and cured at 80°C for 2 hours and at 100°C for 1 hour to obtain a silicone anti-corrosion coating.
[0051] Test Example 1
[0052] Flame retardant performance test
[0053] Test method: The coatings coated with the organosilicon anticorrosive coatings prepared in all the examples and comparative examples were tested using an intelligent critical oxygen index analyzer, and the limiting oxygen index was tested according to standard ASTM D2863-2012. The results are shown in Table 1.
[0054] Table 1
[0055] Limiting oxygen index (%) Example 1 34.1 Example 2 32.7 Example 3 35.5 Comparative Example 1 24.9 Comparative Example 2 26.4 Comparative Example 3 22.1
[0056] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 1, it can be found that the organosilicon anticorrosive coating prepared by the present invention has good flame retardancy.
[0057] By comparison, the limiting oxygen index of Examples 1-3 is greater than that of Comparative Examples 1-3, indicating that modified nano titanium dioxide is prepared by reacting titanium dioxide nanosheets, aniline and (3-aminophenyl)phosphonic acid, and the presence of (3-aminophenyl)phosphonic acid can give the coating flame retardant properties. The epoxy resin, functionalized polysiloxane, xylene, modified nano titanium dioxide and polyamide curing agent are mixed to prepare an organosilicon anti-corrosion coating. The hydroxyl group generated by the ring-opening reaction of the epoxy resin can react with the phenylboronic acid pinacol ester of the side chain of the functionalized polysiloxane to form a borate ester. The presence of the borate ester can also synergistically flame retardant with the phosphorus element in phosphoric acid, further improving the flame retardant properties of the coating.
[0058] Test Example 2
[0059] Antimicrobial performance testing
[0060] Test method: The antibacterial rate of the coatings coated with the organosilicon anticorrosive coatings prepared in all the examples and comparative examples was tested according to the standard QB / T2591-2003. The results are shown in Table 2.
[0061] Table 2
[0062]
[0063]
[0064] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 2, it can be found that the organosilicon anticorrosive coating prepared by the present invention has good antibacterial properties.
[0065] By comparison, the antibacterial rates of Examples 1-3 are greater than those of Comparative Examples 1 and 3, indicating that heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and 4-chloromethylphenylboronic acid pinacol ester are reacted to obtain quaternized cyclotetrasiloxane, the double bonds on N,N-dimethylethyleneamine and the silicon-hydrogen bonds on heptamethylcyclotetrasiloxane are combined by silicon hydrogen addition, and then nucleophilic substitution with 4-chloromethylphenylboronic acid pinacol ester is performed to generate quaternized cyclotetrasiloxane, quaternized cyclotetrasiloxane and octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are ring-opening polymerized to obtain amino-terminated functionalized polysiloxane, and the quaternary ammonium salt structure carried by the polysiloxane side chain can give the coating certain antibacterial properties, and secondly, titanium dioxide nanosheets, aniline and (3-aminophenyl)phosphonic acid are reacted to obtain modified nano-titanium dioxide, and titanium dioxide can also give the coating certain antibacterial properties due to its own photocatalytic activity.
[0066] Test Example 3
[0067] Anti-corrosion performance test
[0068] Test method: With reference to the standard GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes", the salt spray resistance of the coatings coated with the silicone anticorrosive coatings prepared in all embodiments and comparative examples was tested in a YWX_60 salt spray chamber; the salt spray was a 5% by mass NaCl solution with a pH of 6.5-7.2, the temperature was set at 35°C, the test time was 200h, and the appearance of the coating was observed after 200h to record whether there was blistering, cracking, rusting, etc. The results are shown in Table 3.
[0069] Self-healing performance test
[0070] Test method: Use a blade to scratch a crack on the surface of the coating coated with the organosilicon anticorrosive coating prepared in all embodiments and comparative examples, with a crack width of 0.1 mm and a depth of 1.5 mm, place it in an environment of 80°C for 24 hours, and perform the test according to the test method of the anticorrosive performance test, and observe the appearance of the scratched area. The results are shown in Table 3.
[0071] Table 3
[0072]
[0073] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 3, it can be found that the organosilicon anti-corrosion coating prepared by the present invention has good anti-corrosion performance and self-repairing performance.
[0074] By comparison, in the anti-corrosion performance test, the impedance values of Examples 1-3 are greater than those of Comparative Examples 2-3, and in the self-healing performance test, the impedance values of Examples 1-3 are greater than those of Comparative Example 1, indicating that the modified nano-titanium dioxide is prepared by reacting titanium dioxide nanosheets, aniline and (3-aminophenyl)phosphonic acid. The sheet structure of nano-titanium dioxide can effectively block the corrosive medium in the air. The polyaniline wrapped on the surface of titanium dioxide has unique anti-corrosion properties, especially for metal surfaces. The presence of polyaniline forms a dense metal oxide film at the interface between the metal and the polyaniline, thereby protecting the metal; epoxy resin, functionalized polysiloxane, xylene, modified nano-titanium dioxide are reacted to obtain modified nano-titanium dioxide. The organic silicon anti-corrosion coating is prepared by mixing titanium dioxide and polyamide curing agent. During the curing process of the coating, the amino groups at both ends of the polyamide curing agent and the functionalized polysiloxane can co-cure and cross-link the epoxy resin. The hydroxyl groups generated by the ring-opening reaction of the epoxy resin can react with the phenylboronic acid pinacol ester on the side chain of the functionalized polysiloxane to form borate ester. When the coating is cracked or broken by external force, the oxygen bridge originally connected to the boron atom is disconnected under the action of stress, releasing free alcohol groups and boric acid. These free alcohol groups and boric acid can recombine to form new borate ester bonds, giving the coating the ability to self-repair, allowing it to maintain good performance after multiple stress cycles.
[0075] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An organosilicon anticorrosive coating, characterized in that: The organosilicon anticorrosive coating comprises the following components by mass: 40-50 parts of epoxy resin, 10-15 parts of functionalized polysiloxane, 20-30 parts of xylene, 10-12 parts of modified nano titanium dioxide, and 20-30 parts of polyamide curing agent; The functionalized polysiloxane is prepared by first reacting heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and 4-chloromethylphenylboronic acid pinacol ester to obtain quaternized cyclotetrasiloxane, and then reacting quaternized cyclotetrasiloxane, octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain the functionalized polysiloxane. The modified nano titanium dioxide is prepared by reacting titanium dioxide nanosheets, aniline and (3-aminophenyl)phosphonic acid.
2. A method for preparing an organosilicon anticorrosive coating, characterized in that: The preparation method comprises the following steps: (1) Heptamethylcyclotetrasiloxane, N,N-dimethylethyleneamine and toluene are mixed in a mass ratio of 1:1.1-1.3:20-30, heated to 80°C and stirred for 1-1.5h under nitrogen protection at a stirring speed of 200-300r / min, then heated to 100-110°C, 0.2-0.3 times the mass of heptamethylcyclotetrasiloxane of chloroplatinic acid is added, the reaction is continued for 7-8h, and toluene is removed by vacuum rotary evaporation at 0.09MPa and 60°C to obtain tertiary amine-containing cyclotetrasiloxane; (2) Under nitrogen protection, 4-chloromethylphenylboronic acid pinacol ester, tertiary amine-containing cyclotetrasiloxane, potassium iodide, potassium carbonate and toluene are mixed uniformly in a mass ratio of 1:1.1-1.2:0.1-0.2:1.5-1.7:10-12, heated to 80°C, stirred for reaction for 1-2h, and stirred at a speed of 200-300r / min. Toluene is removed by vacuum rotary evaporation at 0.09MPa and 60°C to obtain quaternized cyclotetrasiloxane; (3) Under nitrogen protection, octamethylcyclotetrasiloxane, quaternized cyclotetrasiloxane, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are mixed in a mass ratio of 1:1.2-1.3:0.8-0.9, stirred at 50°C for 10-20 min, a macroporous strongly acidic cation exchange resin of 0.3-0.5 times the mass of octamethylcyclotetrasiloxane is added, the temperature is raised to 60°C, the reaction is continued for 5-6 h, the filtrate is filtered and collected, and the filtrate is evaporated under reduced pressure at 0.09 MPa and 60°C for 3 h to obtain a functionalized polysiloxane; (4) After mixing titanium dioxide nanosheets, polyvinyl pyrrolidone and ethanol for 3-5 minutes, aniline, (3-aminophenyl)phosphonic acid and 1 mol / L sulfuric acid aqueous solution were added, and stirred at a speed of 300-400 r / min for 30-40 minutes, 15 mg / mL ammonium persulfate aqueous solution was added, and stirred at 0°C for 20-22 hours, filtered and dried at 80°C for 6-8 hours to obtain modified nano titanium dioxide; (5) Weigh the following components by mass: 40-50 parts of epoxy resin, 10-15 parts of functionalized polysiloxane, 20-30 parts of xylene, 10-12 parts of modified nano-titanium dioxide, and 20-30 parts of polyamide curing agent, and stir the above components for 3-5 minutes to obtain an organosilicon anti-corrosion coating.
3. The method for preparing an organosilicon anticorrosive coating according to claim 2, characterized in that: The model of the macroporous strongly acidic cation exchange resin in step (3) is HND-580.
4. The method for preparing an organosilicon anticorrosive coating according to claim 2, characterized in that: The preparation method of the titanium dioxide nanosheets in step (4) is as follows: adding hydrofluoric acid to butyl titanate and stirring for 20-30 minutes, the volume ratio of hydrofluoric acid to butyl titanate is 1:5, the stirring speed is 300-400r / min, reacting in a polytetrafluoroethylene reactor at 180°C for 24 hours, cooling to room temperature, washing with pure water for 3-5 times, and drying at 60°C for 10-12 hours to obtain titanium dioxide nanosheets.
5. The method for preparing an organosilicon anticorrosive coating according to claim 2, characterized in that: The amounts of the titanium dioxide nanosheets, polyvinyl pyrrolidone, ethanol, aniline, (3-aminophenyl)phosphonic acid, 1 mol / L sulfuric acid aqueous solution, and 15 mg / mL ammonium persulfate aqueous solution in step (4) are as follows: by mass: 1 part of titanium dioxide nanosheets, 0.6-0.8 parts of polypyrrolidone, 500-550 parts of ethanol, 0.3-0.5 parts of aniline, 0.3-0.5 parts of (3-aminophenyl)phosphonic acid, 20-25 parts of 1 mol / L sulfuric acid aqueous solution, and 50-60 parts of 5 mg / mL ammonium persulfate aqueous solution.
6. The method for preparing an organosilicon anticorrosive coating according to claim 2, characterized in that: The model of the epoxy resin in step (5) is E51; the model of the polyamide curing agent is 650.
7. The method for preparing an organosilicon anticorrosive coating according to claim 2, characterized in that: The organosilicon anti-corrosion coating is prepared and used immediately; the method for using the organosilicon anti-corrosion coating is as follows: applying the coating on a polished and degreased tinplate, curing it at 80° C. for 2 hours and curing it at 100° C. for 1 hour to obtain an organosilicon anti-corrosion coating.
Citation Information
Patent Citations
Preparation method of ultra-thin titanium dioxide nanosheet
CN102010002A
Vinyl terminated polysiloxane containing quaternary ammonium salt, its synthesis and application thereof in preparation of intrinsic quaternary ammonium salt type antibacterial silicone rubber
CN108586751A
Environment-friendly flame-retardant smoke-suppression antistatic filler for waterborne epoxy resin coating and preparation method thereof
CN116200063A
Amino polysiloxane and application thereof in epoxy resin-based expansion fireproof coating
CN116769167A
Antibacterial and antioxidant composition and preparation method of diabetic ulcer dressing
CN118370856A
Cited By
Self-cleaning nano-coating glass plate as well as preparation method and application thereof
CN120098542A
Anticorrosive coating composition and preparation method thereof
CN121518004A
Thermal insulation nanoceramic coating and preparation method thereof
CN122686193A